Testing and modeling dowel and catenary action in rebars crossing shear joints in RC. (15th August 2017) - Sørensen, Jesper H.; Hoang, Linh C.; Olesen, John F.; Fischer, Gregor
Highlights: Experimental results of two-sided dowel joints subjected to shear are presented. The in-elastic displacements are modeled using a second order plasticity model. The normality condition of plastic theory is combined with the kinematic relations. The model provides a tool for robustness assessment of two-sided dowel joints. Abstract: This paper presents a detailed study of the shear behavior of two-sided dowel joints, which includes initiation of dowel action at small shear displacements and development of full catenary action in the reinforcement at large displacements. In addition to experimental results, the paper also presents a simple, second order plasticity model to describe the non-linear regime of the load-displacement relationship. In the model, kinematic relations and the normality condition of plastic theory are utilized to establish a unique link between the imposed shear displacement and combinations of moment and tension that develop in the rebar(s) crossing the joint. Interface friction is included in a consistent manner based on clamping stresses induced by the tension of the rebar(s). Comparison of experimental results with the model predictions shows satisfactory agreement. The model has, due to its simplicity, potential for practical applications related to assessment of structural robustness, where estimation of the available energy (area below load-displacement curve) is important.